Family models and family values in Tuva media discourse - Rostovskaya, Tamara K.; Vasilieva, Ekaterina N.; Kuchmaeva, Oksana V. (The New Research of Tuva, 2025)
The article characterizes family models and family values of the residents of the Republic of Tuva as represented in local mass media. The source of analysis includes episodes of the thematic television program “Family Portrait”, broadcast on the Tuva 24 channel in 2024, as part of the activities of the Year of the Family in Russia. The families participating in the program are characterized as young families (those who married and fulfilled their reproductive plans before the age of 35). They can be classified as multigenerational families since multiple generations participate in child-rearing, with strong interpersonal bonds and care for the older generation being noted. In terms of the number of children, the families include large families, two-child families, and single-child families, some of which have not fully realized their reproductive plans. The relationships between spouses are described as both partnership-based and ambivalent (with the man as the head of the family, but the woman also participating in decision-making). It is noted that the ethnocultural traditions of the titular ethnic group of the Republic of Tuva — the Tuvans — influence the daily practices not only of Tuvan families but also of interethnic families. The program conveys a range of values important to the all-Russian discourse: patriotism, civic responsibility, service to the Fatherland and accountability for its future, strong family bonds, constructive labor, mutual assistance and respect, intergenerational continuity, the unity of the peoples of Russia, etc.